2018
DOI: 10.1007/s12053-018-9618-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating energy efficiency policy: understanding the ‘energy policy epistemology’ may explain the lack of demand for randomised controlled trials

Abstract: Vine et al. 's (2014) call for more randomised controlled trials (RCTs) in government-funded energy efficiency policy evaluation practice raises timely questions about what constitutes effective designs for evaluating and informing energy policy. Their implicit hypothesis that policy organisations share the same epistemic perspective as they do, and that the reason there are few RCTs are due to a set of barriers to be overcome is examined in relation to the UK government Department of Energy and Climate Chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The making use of evaluation results, moreover, hinges upon the timing of the evaluation, especially so in a policy field like energy efficiency that is rapidly developing [51]. As such, the design of the evaluation should mirror the timeframe of the use, where more rapidly executed evaluations may be favourable over more extensive ones at certain occasions, and vice versa.…”
Section: Use Of Evaluationsmentioning
confidence: 99%
“…The making use of evaluation results, moreover, hinges upon the timing of the evaluation, especially so in a policy field like energy efficiency that is rapidly developing [51]. As such, the design of the evaluation should mirror the timeframe of the use, where more rapidly executed evaluations may be favourable over more extensive ones at certain occasions, and vice versa.…”
Section: Use Of Evaluationsmentioning
confidence: 99%
“…As energy resources have appeared more and more precarious, new SSH disciplines have added their respective approaches and bodies of knowledge, creating a heterogeneous group, which addresses energy efficiency from different angles. Today, SSH researchers also help to increase energy efficiency by studying what people and institutions know and do-including those who are tasked with implementing energy efficiency (Cooper, 2018)-as well as reflecting critically on SSH's ability to engage with energy as a technical entity and exploring what changing a society's relationship to energy means in more fundamental terms (Love and Cooper, 2015;Cooper, 2017).…”
Section: Background Context: the Evolution Of Social Sciences And Hum...mentioning
confidence: 99%
“…More research is also needed on other building EEMs, as a recent evidence gap map found that few studies examine government, public or commercial buildings (Berretta et al, 2021). There is debate about the barriers to randomised evaluations in the energy efficiency space (Cooper, 2018; Vine et al, 2014). Even when randomised evaluations are not feasible, natural experiments and quasi‐experimental methods can provide useful causal evidence (Cooper, 2018).…”
Section: Authors' Conclusionmentioning
confidence: 99%
“…There is debate about the barriers to randomised evaluations in the energy efficiency space (Cooper, 2018 ; Vine et al, 2014 ). Even when randomised evaluations are not feasible, natural experiments and quasi‐experimental methods can provide useful causal evidence (Cooper, 2018 ).…”
Section: Authors' Conclusionmentioning
confidence: 99%